Evaluation of oxygen budget and mechanical aeration requirements of red tilapia cage-culture in earthen ponds - Is-haak, Jesada; Kaewnern, Methee; Yoonpundh, Ruangvit; Taparhudee, Wara (Agriculture and Natural Resources, 2020)
The oxygen budget (OB) and aeration requirements were evaluated of red tilapia cage-culture in earthen ponds using two culture ponds (0.48 ha and 0.64 ha) on a commercial fish farm in Pathum Thani, Thailand. These two ponds were installed with two (3 HP) and four (2.5 HP) long-armed paddle wheel aerators, respectively. The data were collected for two consecutive crops (12 wk/crop). The results showed that the OB at night was 3.10 ± 0.08 mg/L, with 93.48 ± 0.88% total oxygen production from the aerators and 76.55 ± 2.01% of the total oxygen was consumed by fish. During the day, the oxygen budget was 10.45 ± 3.49 mg/L, with 67.08 ± 2.95 % from aerators and 91.54 ± 1.13% of the total oxygen was consumed by fish. The maximum power requirement for the aerators at night was 5.00 ± 0.20 HP/ha while during the day, no supplementary aeration was required and so the power requirement then was zero. However, the farmer used aerator power of 14.07 HP/ha for 22.5 hr/d, which exceeded the pond requirements, and the power wastage could be reduced by powering off 50 % of the aerators at night and 100% during the day unless there were a crisis. Thus, increased energy efficiency and a huge cost saving can be achieved in the production cost to farmers.